Concept of Corporate Branding: Challenges and Comparison with Product Branding - Alyafei, Othman (International Journal of Scientific Research and Management (IJSRM), 2022)
Branding is the act of making a strong impression on customers regarding the quality and niche of their product or company. There are many types of branding, but the three most common types of branding are: Corporate branding, Product branding and Personal branding (Jones, 2013). Corporate branding is the act of branding of a corporate body. It allows us to recognize the corporate and their quality product in the market. It helps us to target the most suitable segment of the product for their promotions and marketing. It is also called Umbrella branding (Abratt, 2012). Product branding is a strategic approach to market a specific product and recognize the facts and figures of the product to their customers. In this study, we have highlighted the importance of branding, corporate branding, and product branding. We have discussed the difference and similarities between these two branding types. We have also discussed the challenges in corporate branding and suggested beneficial points in the end to overcome these challenges and to progress in the field of business and marketing by following systematic approach of branding.